Morphofunctional and Biochemical Approaches for Studying Mitochondrial Changes during Myoblasts Differentiation. (14th April 2011) - Barbieri, Elena; Battistelli, Michela; Casadei, Lucia; Vallorani, Luciana; Piccoli, Giovanni; Guescini, Michele; Gioacchini, Anna Maria; Polidori, Emanuela; Zeppa, Sabrina; Ceccaroli, Paola; Stocchi, Laura; Stocchi, Vilberto; et al.
Abstract : This study describes mitochondrial behaviour during the C2C12 myoblast differentiation program and proposes a proteomic approach to mitochondria integrated with classical morphofunctional and biochemical analyses. Mitochondrial ultrastructure variations were determined by transmission electron microscopy; mitochondrial mass and membrane potential were analysed by Mitotracker Green and JC-1 stains and by epifluorescence microscope. Expression of PGC1 α, NRF1 α, and Tfam genes controlling mitochondrial biogenesis was studied by real-time PCR. The mitochondrial functionality was tested by cytochrome c oxidase activity and COXII expression. Mitochondrial proteomic profile was also performed. These assays showed that mitochondrial biogenesis and activity significantly increase in differentiating myotubes. The proteomic profile identifies 32 differentially expressed proteins, mostly involved in oxidative metabolism, typical of myotubes formation. Other notable proteins, such as superoxide dismutase (MnSOD), a cell protection molecule, and voltage-dependent anion-selective channel protein (VDAC1) involved in the mitochondria-mediated apoptosis, were found to be regulated by the myogenic process. The integration of these approaches represents a helpful tool for studying mitochondrial dynamics, biogenesis, and functionality in comparative surveys on mitochondrial pathogenic or senescent satellite cells.